ANALYSIS OF THE HUMAN DEVELOPMENT INDEX (HDI) IN INDONESIA - Yuliansyah Yuliansyah (Cross-Border Journal of Business Management, 2021)
Human Development is a development process that aims to be able to have more choices, especially in health, education and decent living standards. One of the benchmarks can be seen from the Human Development Index. The purpose of this study is to see the achievement of the Human Development Index (HDI) in Indonesia and how the HDI achievement in each province in Indonesia in 2016-2020. The methodology of this research uses a qualitative approach with the type of evaluative research. HDI data in this study is in the form of secondary data issued from the Central Statistics Agency. The results of this study, that Indonesia has an HDI value which increases every year during the 2016-2020 period. And the HDI achievements of each Province have increased very well because in 2020 in Indonesia no one else has a low HDI level.